The Influence of Financial Performance, Environmental Performance, and Governance on Sustainability Reporting: The Moderating Role of Public Demand - Dwiyani, Titik; Sedjati, Dwi Poetra; Widiyaningsih, Vitalis Ari; Putra, Alfa Santoso Budiwidjojo (International Journal of Economics (IJEC), 2025)
This study examines the relationship between financial performance, environmental performance, and corporate governance on sustainability disclosures (sustainability reports). Financial performance is measured using liquidity, solvency, and profitability, whereas environmental performance is measured using environmental costs and the PROPER rating achieved by the company. The corporate governance variable in this study was measured through independent commissioners, audit committees, and institutional ownership. The dependent variable is sustainability disclosure (sustainability reports). This study uses a population and sample of non-cyclical sector companies that published financial statements and sustainability reports from 2021 to 2023. The sample was selected using stratified random sampling, resulting in 135 companies meeting the research criteria. Data analysis employed classical assumption testing and hypothesis testing using the least-squares method. The findings indicate that financial performance, environmental cost-related performance, and institutional ownership significantly influence sustainability reporting. In contrast, PROPER-based environmental performance, independent commissioners, and audit committees did not have a significant effect. The moderating variable, community/media pressure, did not moderate the relationship between the independent and dependent variables. These findings serve as a reference for encouraging better corporate governance practices to support environmental sustainability, thus fostering harmony in environmental preservation